Pengaruh Esktrak Daun Sirsak (Anonna Muricata L.) Terhadap Mortalitas Dan Intensitas Serangan Ulat Grayak (Spodoptera frugiperda J.E. Smith) Pada Tanaman Jagung (Zea mays L.) - Rilista Putri Amalia; Sugiarto Sugiarto; Tatang Surjana (Peneliti.net, 2022)
This study aimed to obtain the right concentration of soursop leaf extract (Annona muricata L.) on mortality and intensity of attack by armyworm (Spodoptera frugiperda) on maize (Zea mays L). This research was conducted at the Center for Forecasting Plant Destruction Organisms (BBPOPT). The research method used is an experimental method using a single factor Randomized Block Design (RAK) consisting of 8 treatments and 5 replications, namely A (Control), B (Synthetic Insecticide Chlorantraniliprole 1.5 ml/l), C (soursop leaf extract 75g /l), D (soursop leaf extract 100g/l), E (soursop leaf extract 125g/l), F (soursop leaf extract 150g/l), G (soursop leaf extract 175g/l), and H (soursop leaf extract 200g/l). The results showed that the soursop leaf extract had a significant effect on the mortality and intensity of the attack of the armyworm Spodoptera frugiperda on maize. Soursop leaf extract starting from a concentration of 100g/l was able to give a significant effect on the intensity of attack and mortality of S. frugiperda so that it can be used as an alternative control on maize (Zea mays L.).